Niger : Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report ;, 2005)
This paper reviews Niger's Poverty Reduction Strategy (PRS) Paper Progress Report. After more than two years of implementation, the PRS has truly become established as the overall framework for the various sectoral strategies in existence or being devised. Moreover, it has been used to focus the actions of all the partners around the government's priorities. Despite the work done, a number of constraints still limit the scope of action. The report also emphasizes the need to continue the reforms by implementing the recommendations of the public expenditure and financial accountability review.